More than Black and White: Differences in Predictors of Obesity among Native Hawaiian/Pacific Islanders and European Americans - Madan, Alok (2012)
Although Native Hawaiians and Pacific Islanders exhibit the highest rates of obesity and associated chronic diseases of any racial/ethnic group, they remain vastly underrepresented in health research. In a cross-sectional survey of college students (N = 402) we examined body mass index (BMI) and health outcomes in an ethnoracially diverse rural sample of Native Hawaiian/Pacific Islanders (25.1%), Asian-Americans (39.8%) and European Americans (35.1%). Measures assessed BMI, health status, health behaviors, frequency of exercise, and symptoms of psychiatric disorders (i.e., depression, anxiety, posttraumatic stress, and substance abuse and dependence). Regression analyses revealed that an overall model of five predictors (gender, race, regular exercise, difficulty sleeping, and anxiety) was significantly associated with obesity (p<0.001) and correctly classified 84.2% of cases. 30.7% of Native Hawaiians/Pacific Islanders were obese as compared to 9.2% of European Americans and 10.6% of Asian Americans. These findings suggest that Native Hawaiian/ Pacific Islanders are at high risk for obesity and associated medical comorbidities, but that regular physical activity may ameliorate this risk. Further, these results support the consideration of Native Hawaiians/Pacific Islanders as a distinct racial/ethnic subgroup separate from other Asian populations.